Analysis of the disclosure of sustainable practices in companies that won the 2024 Anefac award - Santos, Cristina Barbosa dos; Matias-Pereira, José; Rodrigues, Jomar Miranda (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To analyze the level and nature of environmental disclosure present in the Management Reports of companies awarded the ANEFAC Transparency Prize in 2024. Methodology: This descriptive and documentary study adopted a quantitative approach, using the Environmental Disclosure Index (EDI) proposed by Bachmann et al. (2013) as a reference. The sample comprises 30 Management Reports from publicly and privately held companies nominated for the ANEFAC Transparency Trophy in 2024. Results: It was found that the most disclosed environmental data relate to long-term management policies and programs, while the least reported items concern environmental protection reserves. Descriptive analysis revealed an average of 71% environmental disclosure, which is considered satisfactory among the groups evaluated by the EDI. It was observed that higher-revenue companies tend to report higher levels of environmental disclosure, using this practice as a strategy to build their image, enhance their reputation with investors, and consequently improve their results. Contributions of the Study: The research expands accounting and socio-environmental literature by demonstrating that companies awarded by ANEFAC in 2024 use environmental disclosure as an instrument of legitimacy and transparency. Furthermore, it provides insights for managers and regulators by highlighting socio-environmental transparency as a competitive differentiator, supported by strengthened stakeholder trust and the consolidation of a sustainable corporate image.